Modeling the Number of Pneumonia in Toddlers in East Java Province in 2021 with Generalized Poisson Regression - Fittrofin Amalia Farisa; Syarifah Nisrina Hasna Salby; Annisa Auliya Rahman; Purhadi Purhadi (Inferensi, 2023)
Pneumonia is one of the highest causes of toddler’s mortality, including Indonesia. In East Java 2021, the discovery of pneumonia is 50%. It is relatively high, especially among children under five. This study aimed to obtain the factors that influence the number of pneumonias in toddlers in East Java by using Generalized Poisson Regression (GPR) model with and without exposure variable. GPR is used when the assumption of Poisson regression is not met due to the overdispersion. Data was obtained from the East Java province health office containing the number of Pneumonia patients in East Java by districts/cities and the factors that allegedly affect them. Based on the analysis, GPR with exposure variable is better than GPR without exposure variable. The possible GPR models with exposure that has the smallest AICc is model that included the percentage of low-birth-weight babies, percentage of coughing/difficulty breathing toddlers given standard management, and percentage of toddlers getting vitamin A. All independent variables included in the model has significance effect to the number of pneumonias in toddlers.